Asthma in pregnant woman and its management : a review - Farni Yuliana Pratiwi; Hadiatussalamah; Intan Adevia Rosnarita; Yuda Anzas Mara; Novia Ariani Dewi (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2023)
Asthma is the most common comorbidity in pregnant women and gives 30% of exacerbation experience. The other 30% will see improvement of their symptoms, and the rest will not see the changes. Exacerbations have become a major clinical concern in pregnant women. Medical concerns for the mother and the childbirth included low birth weight, preeclampsia, and preterm delivery. The major goal is to keep asthma under control to ensure mother's health and well-being, as well as fetal growth. Controlling asthma and preventing exacerbations are the main goals of asthma treatment during pregnancy. Treatment for asthma should ideally begin before conception. This is to avoid day-time and night-time symptoms, as well as to keep lung function. Furthermore, fetal oxygenation is a crucial factor during the pregnancy. With a few exceptions, asthma drugs are basically the same in pregnancy as they are in non-pregnant people. Inhaled corticosteroids (ICS) are often used as a controlling treatment. Budesonide is the recommended ICS. Short-acting β-agonist (SABA) preferable as reliever in acute asthma and to relieve exacerbation. As an add-on therapy for medium to high dose ICS, long-acting β-gonists (LABA) is often used. Virus infections and ICS nonadherence are the two most common causes of asthma exacerbations during pregnancy.